IDHwt Glioblastomas Show Opposing Resistance Mechanisms Across Patients in Response to Standard Treatment. (1st October 2022) - Tanner, Georgette; Finetti, Martina A; Pollock, Steven; Rippaus, Nora; Bruns, Alexander-Francisco; Hogg, Catherine; Droop, Alastair; Bruning-Richardson, Anke; Care, Mathew; Wilkinson, Joseph; Jenkinson, Michael; Brodbelt, Andrew; et al.
Abstract: AIMS: Glioblastoma (GBM) is the most common primary malignant brain tumour in adults. Despite aggressive treatment, a resistant tumour recurs in practically all patients. We therefore aimed to better understand the mechanisms driving this treatment resistance through investigating changes in gene expression across pairs of primary and recurrent GBM tumours. METHOD: We generated or acquired bulk tumour RNA sequencing data for primary and first recurrent tumours from 107 patients who received standard treatment. Differential expression analysis between primary and recurrent samples found that the most dysregulated genes were involved in neurodevelopment and neurodifferentiation. We therefore used a publicly available ChIP-seq database to identify DNA binding factors for which binding sites are enriched in the promotors of genes with the largest expression changes from primary to recurrent. RESULTS: Jumonji and AT-Rich Interacting Domain 2 (JARID2) was the most strongly enriched for binding to promotors of dysregulated genes. 65 patients showed an up-regulation and 42 showed a down-regulation of genes bound by this protein. The same set of JARID2 bound genes were found to be dysregulated in each direction, and correlated with the largest source of variation between samples in their response to treatment. Further enrichment analyses indicated that 'Up' responders may resist treatment through reduced proliferation and increased interaction with the tumour microenvironment, whereas 'Down' responders instead rely on a shift to mesenchymal cell states. CONCLUSION: These results indicate that GBM tumours can be split into two subtypes that transcriptionally reprogramme in different directions through treatment and may benefit from different treatment approaches.